Medical Tourism Management - Bentley, Leo (RADINKA JAYA UTAMA PUBLISHER, 2024)
Medical tourism, the practice of traveling abroad for medical treatment, has gained substantial attention in recent years due to its implications for healthcare delivery and tourism industry dynamics. This paper investigates the management strategies employed in medical tourism destinations, focusing on enhancing healthcare services and tourism competitiveness. Utilizing secondary data from scholarly articles, reports, and industry publications, the research synthesizes existing knowledge on medical tourism management frameworks, destination competitiveness factors, patient experiences, and healthcare quality metrics. The study employs a qualitative analysis approach to distill key insights and patterns from the literature, shedding light on effective management practices and their impact on patient outcomes and destination attractiveness. Findings reveal the importance of strategic planning, collaboration between healthcare providers and tourism stakeholders, quality assurance mechanisms, and marketing strategies in optimizing medical tourism experiences. The paper discusses implications for policy development, industry regulations, and sustainable growth strategies in medical tourism destinations. By leveraging secondary data sources, this research contributes to a comprehensive understanding of medical tourism management dynamics, offering practical insights for healthcare providers, policymakers, and tourism professionals navigating this evolving landscape. Keywords- Medical tourism, Management strategies, Destination competitiveness, Healthcare quality